CH.AYTMATOV AS A NEW NATURE OF INTERCULTURAL AND INTERRELIGIOUS DIALOGUE IN THE INTEGRATED SOCIAL-PLANETARY SYSTEM (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Ch.Aytmatov was a personality of a planetary scale who was appropriately accepted within the human history. He continues to live among us in his philosophic-literary ideas, works, and examples. From this position the author of the article suggests looking through the social-philosophic views of Ch.Aytmatov as a new base for intercultural and interreligious dialogue in the context of modern global problems.